2016
DOI: 10.1002/adfm.201604040
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Dynamics of Two‐Dimensional Layered Materials

Abstract: The growing library of two-dimensional layered materials is providing researchers with a wealth of opportunity to explore and tune physical phenomena at the nanoscale. Here, we review the experimental and theoretical state-of-art concerning the electron spin dynamics in graphene, silicene, phosphorene, transition metal dichalcogenides, covalent heterostructures of organic molecules and topological materials. The spin transport, chemical and defect induced magnetic moments, and the effect of spin-orbit coupling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 343 publications
0
8
0
Order By: Relevance
“…25,26 Moreover, the strong SOC effect and the breaking of inversion symmetry for monolayer TMDs also promote the research works on their spintronic applications, especially for the generation of SOT. [27][28][29] Current induced field-like and damping-like torques were observed in Py/MoS2 bilayers and the strong SOT exhibited purely interfacial nature. 30 A further study has experimentally shown that one can change the allowed symmetries of SOT in spin-source/ferromagnet bilayer devices with low crystalline symmetry.…”
mentioning
confidence: 93%
“…25,26 Moreover, the strong SOC effect and the breaking of inversion symmetry for monolayer TMDs also promote the research works on their spintronic applications, especially for the generation of SOT. [27][28][29] Current induced field-like and damping-like torques were observed in Py/MoS2 bilayers and the strong SOT exhibited purely interfacial nature. 30 A further study has experimentally shown that one can change the allowed symmetries of SOT in spin-source/ferromagnet bilayer devices with low crystalline symmetry.…”
mentioning
confidence: 93%
“…Moreover, in a phosphorene ribbon, the edges terminated with zigzag or armchair configuration as well as functional groups have a different bandgap as compared to its microscale counterpart. The ease of bandgap tunability in phosphorene renders it a rich platform for novel physical phenomena such as the integral quantum hall effect, superconductivity, fermions, spintronics, and topological insulators …”
Section: Introductionmentioning
confidence: 99%
“…Graphene is having a groundbreaking impact on science and technology, owing, in particular, to the high mobility of its charge carriers, together with its flexibility, high specific surface area, and thermal conductivity . After the advent of graphene, an abundant number of 2D materials, together with their heterostructures, have attracted the interest of the scientific community, due to their application capabilities, which are often superior to those of graphene . Moreover, many layered materials also exhibit topological properties with implications for various disciplines …”
Section: Introductionmentioning
confidence: 99%